Constraining the Venus Interior Structure with Future VERITAS Measurements of the Gravitational Atmospheric Loading - Cascioli, Gael; Renaud, Joe P.; Mazarico, Erwan; Durante, Daniele; Iess, Luciano; Goossens, Sander; Smrekar, Suzanne (IOP, 2023)
The complex dynamics of the Venus atmosphere produces a periodic mass redistribution pattern that creates a time-variable modulation of the gravity field of Venus. This gravity signal depends on the net transport of mass across the globe and on the response of the solid body to the normal loading of its crust imparted by the atmosphere. In this work, we explore the possibility of measuring this phenomenon with VERITAS, a NASA Discovery-class mission. By simulating the gravity science experiment, we explore the possibility of measuring the response of Venus to the atmospheric loading, parametrized by the loading Love numbers (𝘬ₗ'), and assess the dependence of these parameters on fundamental interior structure properties. Using the most recent models of Venus' interior, we compute the Venus Love numbers in a compressible viscoelastic setting and compare them with the predicted uncertainty of the VERITAS measurements. We show that VERITAS will measure 𝘬₂' at the 4% level and that this measurement could possibly help to distinguish between different equally plausible interior structure models, especially allowing us to distinguish different rheological laws. We also show that a measurement campaign such as the VERITAS gravity science investigation has the potential of measuring 𝘬₂' not only at the loading forcing frequency, but also at the tidal frequency, ultimately providing a way to probe the response of the planet at different forcing periods.